El desarrollo de destrezas y habilidades en la motricidad gruesa en niños y niñas de 24 a 36 meses del centro infantil del buen vivir infancia feliz - Herrera Yugcha, Leslie Anahí (2017)
The present investigation has the goal of understanding as well as highlight the importance of psychomotor development in girls and boys. Also, the influence of this process in the scholarship through a good stimulation of the gross motor area. For this reason, the investigation has considered this point of view due to the kits are starting and discovering their learning process base of their own senses and movements. Moreover, the investigation is looking for determine the motor stimulation importance through the acquisition of motor skills in order to an adequate development in the psychomotor process. Nowadays some problems are considering such us: available work area to work with them, and specific planning of teachers for this area of skill. Consequently; it was observe lack of student´s development in this space. The interview, survey and observation sheet were the instruments that allowed collect information as well as measure and contribute with the psychomotor development. The materials used to apply the observation sheet were suitable because it was according to the boys and girls age. It permits asses the level of their psychomotor development….